Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada Es Teh Indonesia Cabang Cipadu Tangerang - Nurul Izzah Mulyani; Amirudin (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Service Quality and Product Quality on Customer Satisfaction at Es Teh Indonesia Cipadu Tangerang Branch. This research uses a quantitative method. The respondents in this study amounted to 100 people. The analysis in this study uses the SPSS version 26 program. The data analysis methods used are simple linear regression, multiple linear regression, correlation coefficient, determination coefficient, partial t-test, and simultaneous F-test. The results of the study indicate that: (1) There is a positive and significant effect of the service quality variable on customer satisfaction at Es Teh Indonesia Cipadu Tangerang Branch, as evidenced by the value of t_calculated > t_table (-1.902 > 1.660) with significance (0.060 < 0.1). (2) There is a positive and significant effect of the product quality variable on customer satisfaction at Es Teh Indonesia Cipadu Tangerang Branch, as evidenced by the value of t_calculated > t_table (10.069 > 1.660) with significance (0.000 < 0.1). (3) Simultaneously, there is a positive and significant effect of service quality and product quality on customer satisfaction at Es Teh Indonesia Cipadu Tangerang Branch, as shown by the result of F_calculated > F_table (63.545 > 2.36) with significance (0.000 < 0.1). (4) The results of the determination coefficient test show an Adjusted R square value of 0.558, which means that simultaneously, the service quality and product quality variables contribute 55.8% to the customer satisfaction variable, while the remaining 44.2% is influenced by other variables.